2004
DOI: 10.1097/00000542-200412000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Proper Shoulder Position for Subclavian Venipuncture

Abstract: Lowered shoulder position increases both overlap and proximity between the clavicle and the subclavian vein, producing a more constant relation between the clavicle and the subclavian vein, without affecting vein diameter. Proper use of a lowered shoulder position should thus increase the safety and reliability of subclavian venipuncture compared with other shoulder positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Turning the head away from the needle puncture site increases the angle of the SCV and IJV, and causes malpositioning in the IJV [8,10]. Lowering the shoulder position reduces the angle between the SCV and innominate vein, and increases the incidence of catheter misplacement into the ipsilateral IJV [9,10]. In the present study, subclavian venous cannulation was performed with the head and shoulders in a neutral position to exclude any positional effect.…”
Section: Discussionmentioning
confidence: 99%
“…Turning the head away from the needle puncture site increases the angle of the SCV and IJV, and causes malpositioning in the IJV [8,10]. Lowering the shoulder position reduces the angle between the SCV and innominate vein, and increases the incidence of catheter misplacement into the ipsilateral IJV [9,10]. In the present study, subclavian venous cannulation was performed with the head and shoulders in a neutral position to exclude any positional effect.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter insertion through the SCV is frequently performed in the ED, and catheter tip malpositioning should be avoided for improving patient prognosis. Previous studies of SCV catheter insertion mostly focused on factors associated with successful puncture of the SCV, catheterization failure, and positions of the malpositioned catheter tips along with the associated complications [ 1 , 4 , 8 , 19 , 24 , 25 ]. In the present study, we attempted to associate incidences of misplacement with radiographic features of patient shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative study of shoulder position based on computed tomography images in the context of catheter misplacement was performed by Kitagawa et al [ 19 ]. They found that a superior-inferior change of 5 cm in shoulder height increased the overlapping area between the clavicle and SCV from 33.5% to 40%, increased the angle between the SCV and IJV from 89° to 117°, and decreased the angle between the SCV and BCV from 114° to 99° in the neutral shoulder position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the risk of catheter passing in to 14,15 the internal jugular vein and vice versa. in the same way the angle between the subclavien vein and innominate vein is reduced by lowering the shoulder posi on and this 16 increases the risk of malposi on. Another effec ve method for minimizing the malposi on from subclavian to internal jugular vein is to apply external pressure on IJV during the threading of the guide wire.…”
Section: 85±1170mentioning
confidence: 96%